KAJIAN TAFSIR TEMATIK KONTEMPORER: Analisis Terhadap Metode Tafsir Tematik Ayat-ayat Psikologis Karya Moh. Abdul Kholiq Hasan - Ervi Marafaniza; Moh. Abdul Kholiq Hasan (Institut Agama Islam Syubbanul Wathon Magelang, 2023)
Thematic interpretation of psychological verses is the work of Moh. Abdul Kholiq Hasan published after Tafsir Rabbana. This interpretation is written to to form it simpler for somebody to get it the relationship of verses in the Quran. This tafsir work was written by Hasan who did not have a psychology education background. So that the author is interested in doing this research aims to see how Hasan sorts out the verses of psychology in the Quran. The author tries to explain the intellectual journey of the mufassir, the works of the mufassir and the results of the analysis of the thematic interpretation method of psychological verses using Baidan's interpretation theory. The results of this study explain that Hasan wrote this work because of the demands as a lecturer and became an alternative for students who are not accustomed to reading the interpretation of the Koran as a whole because the method used is thematic which examines verses with certain themes and uses psychological patterns.